Citizenship Education as a Democracy Learning for Students in Higher Education - Agil Nanggala (Universitas Muhammadiyah Mataram, 2020)
Citizenship Education is a form of learning democracy both theoretically and practically because the scientific structure is very supportive in forming democratic and Pancasila students. This study uses a qualitative approach with the method of literature study because it is in the form of an analysis of the concepts and dynamics of Citizenship Education as learning democracy in college students. There are also the results of research, are as follows: 1) The implementation of learning democracy, through Citizenship Education is highly dependent on the curriculum of each college, 2)Contextual learning is very suitable in implementing democational learning through Citizenship Education because it has almost the same characteristics in the object of study learning, 3) As a democracy learning Citizenship Education has a strategic position in the national constitution and curriculum, although tertiary institutions have the authority in preparing their curriculum, the position of Education Citizenship as a compulsory subject is irreplaceable, 4) The importance of creating a democratic atmosphere so that learning objectives can be achieved effectively, because it is not only through an explanation of democratic material, conceptually and theoretically, but in practice, so the integrity of lecturers and students is needed.